Effects of phosphate solubilizing bacteria, phosphate sources and organic acid on growth promotion of aerobic rice - Panhwar, Qurban Ali (2011)
Phosphate-solubilizing bacteria (PSB) are frequently used as plant growth promoters and known to be able to solubilize different forms of inorganic phosphates. A series of experiments were conducted in laboratory and glasshouse conditions with the following objectives; i) to isolate and characterize the PSB strains from aerobic rice, ii) to evaluate the colonization of PSB on aerobic rice roots, iii) to evaluate the efficacy of PSB for production of organic acid from different sources of phosphate (P) in aerobic rice, iv) to determine the effect of combined PSB strains with organic acids on solubilization of P from phosphate rock and v) to determine the efficiency of P uptake and plant growth promotion of aerobic rice by PSB from phosphate rock using 32P technique. Forty three PSB strains were isolated from aerobic rice (Oryza sativa L.). Sixteen potential PSB strains tested and characterized in in vitro condition for P solubilization activity. Root colonization of the PSB strains was visually observed by using Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). Glasshouse studies were conducted to evaluate the ability of strains Bacillus spp. (PSB9 and PSB16) to produce organic acids from different sources of P fertilizers and the effect of diffrerent rates of dominant organic acids with PSB inoculation on solubilization of Christmas Island Phosphate Rock. The 32P isotopic dilution technique was used to determine the efficiency of plant P uptake. The population of isolated PSB strains from aerobic rice was significantly (P<0.05) higher in rhizosphere than in non-rhizosphere soil. The P solubilizing activity of strains differed in different phosphate media used with the highest P solubilization observed in NBRIP broth containing calcium phosphate, while comparatively lower P observed in CIPR, and in PDYA-AlP containing aluminum phosphate. The P solubilization rate of different phosphate forms followed the first order kinetics. The bacterial strains were able to produce different organic acids (oxalic, malic, succinic and propionic acids) and in addition produce indole acetic acid (IAA), and enzymes (phosphatase and phytase). In general, the P solubilization by the different bacterial strains were significantly (P<0.05) influenced by the P sources used. The SEM and TEM micrographs proved that the PSB strains were able to colonize on surfaces and interior of rice roots. The PSB strains inoculated to rice plants under glasshouse conditions were able to produce organic acids and enhance P solubilization from CIPR. Exogenous oxalic acid application solubilized higher P (31.51%) of CIPR than the malic acid and this significantly affected growth of aerobic rice. The isotopic 32P dilution studies proved that applied PSB strains were able to release P ions either from the added CIPR or from the less available indigenous P in soil resulting in higher plant P uptake and higher grain yield (37.87% over control). Inorganic fractionations of P in soil were ranked in the descending order of Fe-P > Al-P > Ca-P > soluble P. This study proved that PSB inoculation enhanced P solubilization from the different P sources through production of organic acids which enhanced P acquisition for growth improvement of aerobic rice.